Method and example of calculation of combined reinforced bending elements (Academic journal Industrial Machine Building Civil Engineering, 2020)
A method for calculating rectangular cross-section bending elements, reinforced with ordinary and prestressed reinforcement, as well as steel fiber, based on the deformation method. This takes into account stress losses in the reinforcement from creep deformations and shrinkage of steel-fiber-concrete. The increase in compressive strength of reinforced concrete under biaxial compression conditions is also taken into account. The bearing capacity calculation results of a standard road plate P60.38 and a similar plate with metal fiber are given.
Keywords: bearing capacity; steel-fiber-concrete; bending moment; curvature; prestressed reinforcement; relative deformations; stresses in reinforcement; stresses in steel-fiber-concrete